Determination of Phytochemical Properties and Antimicrobial Activities of Oregano vulgare against MRSA - Iqubal, S. M. Shakeel (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: The focus of this study is to test the antibacterial activity of one such essential oils derived from Oregano vulgare (O. Oregano) culinary herbs belongs to Lamiaceae family, against the MRSA nosocomial infections and also determine the phytochemical properties of the herb. Our study is based on the MRSA nosocomial infection. The major concern of the nosocomial infection with MRSA is that majority of the cases were not curable with any drug due to the evolution of the abuse of antibiotics. Many bacteria not only Staphylococcus aureus have become resistant in the recent past to the multiple antibiotics. Materials and Methods: The phytochemical properties analysis of the Oregano essential oil procured from the local market was determined by the standard biochemical methods. The MRSA clinical specimens were procured from the nosocomial infected patients. Antibacterial activity was carried out. Results and Discussion: O. vulgare essential oil procured from the local market shown jubilant antibacterial activity results [Table 1] against all the clinical isolates with an average disk diffusion of 21 mm zone of inhibition diameter obtained from performing the Kirby–Bauer technique with an average MIC value of 0.88 μ/ml and an average MBC value of 1.13 μ/ml. The best susceptibility of MRSA clinical isolate was observed in nasal swab sample with a zone diffusion of 27 mm with MIC of 0.5 μ/ml and MBC of 0.75 μ/ml toward O. vulgare essential oil. Conclusion: Our study concludes that phytochemical compounds present in O. vulgare essential oil analyzed using biochemical tests and these phytochemical compounds act as an effective remedy toward the MRSA clinical isolates and shown significant results in the study when compared to the standard antibiotics for the same clinical isolates which shown variable subsidized results. The susceptibility result values of O. vulgare essential oil shown that it may require lower dosage values when compared to that of the standard antibiotics for the same clinical isolates. This study recommends the use of natural essential oils from the plant source as an alternative toward the chemical antibiotics with more detailed studies need to be done in near future with the expectations that many dangerous infections can be cured with these types of phytochemical compounds.